2013
DOI: 10.5897/jen2013.0073
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of insecticidal activities of Mentha piperita and Lavandula angustifolia essential oils against house fly, Musca domestica L. (Diptera: Muscidae)

Abstract: The essential oils of peppermint, Mentha piperita and lavender, Lavandula angustifolia were tested for their larvicidal and pupicidal activities against the house fly, Musca domestica L. (Diptera: Muscidae). The effects of the two lethal concentrations LC50 and LC75 on the larval duration, pupation percent, pupal duration and adult emergence were also determined. In addition, the induced malformation at larval and pupal stages were recorded and photographed. The results about M. piperita showed higher toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…(Table 2). The insecticidal activity of Mentha piperita Linnaeus and Lavandula angustifolia Mill essential oils were evaluated against house fly and induced a significant prolongation in larval and pupal periods (BOSLY, 2013). In contrast, the duration of the larval, pupal and newly-hatched larvae to adult periods of M. domestica with citral treatment were faster in the presence of this substance (3.18; 4.91; 7.91 days respectively), showing a significant difference (P <0,0001) when compared to the control groups (larval period:…”
Section: Bioassaysmentioning
confidence: 99%
“…(Table 2). The insecticidal activity of Mentha piperita Linnaeus and Lavandula angustifolia Mill essential oils were evaluated against house fly and induced a significant prolongation in larval and pupal periods (BOSLY, 2013). In contrast, the duration of the larval, pupal and newly-hatched larvae to adult periods of M. domestica with citral treatment were faster in the presence of this substance (3.18; 4.91; 7.91 days respectively), showing a significant difference (P <0,0001) when compared to the control groups (larval period:…”
Section: Bioassaysmentioning
confidence: 99%
“…As a general trend, our data indicated that pupation and adult emergence are adversely affected after treatment of sheep blowfly larvae with sublethal concentrations of EOs. In the same token, EOs led to comparable growth inhibition of myiasis producing flies as well as other insects of medical and veterinary importance had been recorded.…”
Section: Discussionmentioning
confidence: 71%
“…Consequently, thought-provoking plant-based products became inspirational to researchers to study the potential insecticidal actions of these products. Among numerous plant species, the aromatics urged the attention by their characteristic odor and flavor (5). Overtime, essential oils were extracted and used for several medicinal and spiritual purposes (6).…”
Section: Introductionmentioning
confidence: 99%